Using Soil P Tests and P-Sorption Index to Predict P Requirement for Cassava Grown in Tropical Upland Sandy Soils. Issue 3 (4th February 2023) - Ratanavirakul, Pinyaluk; Thanachit, Suphicha; Anusontpornperm, Somchai; Kheoruenromme, Irb
ABSTRACT: The phosphorus (P) sorption index and efficiency of P extracting methods were investigated to quantify the available P content for accurate recommendations regarding cassava P fertilizer application in the sandy soils of Thailand. Phosphorus sorption isotherms were examined to predict the response of soils to the P fertilizers applied. Six rates of P fertilizers (0, 12.5, 25, 37.5, 50 and 62.5 kg P2 O5 ha −1 ) were applied in a randomized complete block design at five field sites in major cassava-growing areas. The efficiency among the Bray II, CaCl2 and Mehlich III extracts was also tested by comparing their capacity to predict crop response. The P adsorption capacities of all soils were in the range 39.4–106 mg kg −1 ; therefore, there were classified as low P -sorbed soils. Phosphorus fertilizer produced significantly higher aboveground biomass than did zero-P fertilization. The critical P level adequate for 95% of the maximum yield was in the range 0.14–0.26 mg P L −1 . The equation for calculating P fertilizer using soil P extracted based on the Bray II, CaCl2 and Mehlich III methods had accuracy levels of 73, 65 and 72%, respectively. Bray II was slightly superior to Mehlich III for use in soil-P availability indices, both of which were recommended for P fertilizer assessment.